Inheritance of two types of modified leaf venation in sunflower (Helianthus annuus L.) - Soroka, A. I.; Lyakh, V. A. (The Indian Journal of Genetics and Plant Breeding, 2016)
The inheritance of two types of modified leaf venation which were called as fan-nerved venation was studied in the cultivated sunflower.Both types of modified venation were isolated in chemical mutagenesis experiments which were conducted earlier. A distinctive feature of one of the mutations is clear appearance of central rib while the second mutation lacks it.The F1 plants from crosses between those mutants and between the mutants and genotypes with reticulate leaf venation had the usual reticulate leaf venation of sunflower (the wild type). The test of allelism, thus, demonstrates that the venation in the induced mutations is controlled by a gene (or genes) different from the gene causing the other venation phenotype. The F2 segregated into four phenotypic classes of leaf venation: reticulate, two groups of both types of modified venation, and plants with the two modified venation types combined in the ratio of 9 reticulate (double dominant phenotype) : 3 fan-venation type 1 : fan-venation type 2 : 1 combined fan-venation (double recessive homozygotes). It is concluded that two non-allelic recessive genes with complementary interaction are involved in the genetic control of fan-nerved leaf venation, and reticulate venation was determined by a combination of at least two dominant alleles of these genes. The gene symbols proposed are vf1 and vf2.